The Impact of Major Powers on Security Council Decisions - Husein, Haidar Salem Abdul; Baqir, Osama Murtadha (Journal of Ecohumanism, 2024)
The research examines the impact of major powers on the work of the Security Council and its impact on international politics. The research emphasizes that the five permanent members of the Council (the United States, Russia, China, France, and the United Kingdom) have veto power, which allows them to prevent any decision even if it has the support of the majority. Major Powers utilize this power strategically to direct international policies according to their interests, which leads to influencing decisions related to international peace and security. The research also identifies how geopolitical balances and strategic interests can sometimes explain the lack of consensus in the Council’s decisions. In addition, the research discusses criticisms of the present structure of the Security Council. It shows reform calls aimed at improving international representation and reducing the influence of major powers to ensure greater effectiveness and justice in dealing with global crises.